(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This study examined the relationship between service quality and visitors’ behavioural intention at selected eco-tourism destinations in South-South Nigeria, specifically Obudu Mountain Resort, Cross River State, and Finima Nature Park, Rivers State. Anchored on the Expectancy Disconfirmation Paradigm, the study adopted a descriptive cross-sectional survey design. Three dimensions of service quality (tangibility, responsiveness, and reliability) were examined as predictors of visitors’ behavioural intention. A structured questionnaire employing a 4-point Likert scale was administered to a sample of 213 visitors across both destinations, drawn using convenience sampling. Of the questionnaires distributed, 200 were retrieved and analysed using Pearson Product Moment Correlation Coefficient via SPSS version 25. Reliability of the instrument was confirmed using Cronbach’s Alpha, with coefficients ranging from 0.71 to 0.81. Findings revealed significant positive relationships between all three dimensions of service quality and visitors’ behavioural intention. Tangibility recorded the strongest association, followed by responsiveness and reliability. The study concludes that enhancing the physical environment, staff responsiveness, and service consistency at eco-tourism sites is essential for sustaining positive visitor behavioural intentions. Recommendations include investment in physical infrastructure, targeted staff training, and robust service delivery frameworks tailored to the eco-tourism context.